PENGARUH PENGGUNAAN MEDIA RODA PINTAR TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 4-5 TAHUN DI TK ISLAM ANNAJAH JAKARTA TIMUR - Anabilah Zelinda Rengganis; Astuti Darmiyanti; Ine Nirmala (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early reading instruction for Group A children (aged 4–5 years) should ideally be implemented in a gradual and simple manner to avoid complex or overly demanding approaches. In reality, children's reading development is heterogeneous; some children have achieved fluency, while others still experience difficulties even in recognizing their own names due to challenges in identifying letter symbols and sounds. To overcome these literacy constraints, educators require innovative instructional media to ensure the teaching and learning process runs effectively, interactively, and meaningfully. This study is oriented toward examining the application of the "smart wheel" media as a solution to stimulate the reading skills of children aged 4–5 years. Utilizing a quantitative approach with a pre-experimental design (One-Group Pre-test Post-test design), this study involved 14 children as research subjects. The analysis results of this study prove that the utilization of "smart wheel" media exerts a positive and significant impact on stimulating the early reading skills of early childhood at Annajah Islamic Kindergarten.